Intranasal powder live attenuated influenza vaccine is thermostable, immunogenic, and protective against homologous challenge in ferrets - Jasmina M. Luczo; Tatiana Bousse; Scott K. Johnson; Cheryl A. Jones; Nicholas Pearce; Carlie A. Neiswanger; Min-Xuan Wang; Erin A. Miller; Nikolai Petrovsky; David E. Wentworth; Victor Bronshtein; Mark Papania; et al. (npj Vaccines, 2021)
Abstract Influenza viruses cause annual seasonal epidemics and sporadic pandemics; vaccination is the most effective countermeasure. Intranasal live attenuated influenza vaccines (LAIVs) are needle-free, mimic the natural route of infection, and elicit robust immunity. However, some LAIVs require reconstitution and cold-chain requirements restrict storage and distribution of all influenza vaccines. We generated a dry-powder, thermostable LAIV (T-LAIV) using Preservation by Vaporization technology and assessed the stability, immunogenicity, and efficacy of T-LAIV alone or combined with delta inulin adjuvant (Advax™) in ferrets. Stability assays demonstrated minimal loss of T-LAIV titer when stored at 25 °C for 1 year. Vaccination of ferrets with T-LAIV alone or with delta inulin adjuvant elicited mucosal antibody and robust serum HI responses in ferrets, and was protective against homologous challenge. These results suggest that the Preservation by Vaporization-generated dry-powder vaccines could be distributed without refrigeration and administered without reconstitution or injection. Given these significant advantages for vaccine distribution and delivery, further research is warranted.